2012
DOI: 10.1007/s00449-012-0799-9
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an amperometric TG biosensor based on AuPPy nanocomposite and poly (indole-5-carboxylic acid) modified Au electrode

Abstract: A method is described for construction of an amperometric triglyceride (TG) biosensor based on covalent co-immobilization of lipase, glycerol kinase and glycerol-3-phosphate oxidase onto gold polypyrrole nanocomposite decorated poly indole-5-carboxylic acid electrodeposited on the surface of a gold electrode. The enzyme electrode was characterized by transmission electron microscopy, scanning electron microscopy, electrochemical impedance studies, Fourier transform infrared spectroscopy and cyclic voltammetry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…This optimum pH is similar to studies reported before, which used amperometry and electrochemical methods [35,36]. However, a different optimum pH is reported by Narang et al [37]. This difference can be caused by a different membrane matrix, type of substrate, enzyme, and immobilization method [38].…”
Section: The Effect Of Buffer Concentration Ph and Loading Enzyme Csupporting
confidence: 88%
“…This optimum pH is similar to studies reported before, which used amperometry and electrochemical methods [35,36]. However, a different optimum pH is reported by Narang et al [37]. This difference can be caused by a different membrane matrix, type of substrate, enzyme, and immobilization method [38].…”
Section: The Effect Of Buffer Concentration Ph and Loading Enzyme Csupporting
confidence: 88%
“…Fabricated electrodes exhibited ultrasensitivity and fast response to dopamine and enables the RP as a suitable enzyme system for dopamine detection in an aqueous solution. 283 . For TG concentrations in the range of 50-700 mg/dl, a linear response was observed.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…The = CH-N stretching vibration of the monomer near 890 cm −1 disappeared in the polymer spectrum. The peaks near 1,478–1,838 cm −1 showed the presence of carboxyl groups in the monomer I-5-CA and the polymer PI-5-CA ( Narang et al, 2013 ). Compared with the FT-IR spectra of PI-5-CA, the FT-IR spectra of PI-5-CA/C-SWCNT nanocomposites showed a one-point positive shift in the C=C bond, which should be attributed to the π–π interaction between PI-5-CA and C-SWCNTs ( Yang et al, 2019 ).…”
Section: Characterization Of the Pi-5-ca/c-swcnts Compositementioning
confidence: 99%